Habitat patch size modulates terrestrial mammal activity patterns in Amazonian forest fragments - Norris, Darren [UNESP]; Michalski, Fernanda [UNESP]; Peres, Carlos A. (Alliance Communications Group Division Allen Press, 2010)
Understanding how environmental change influences the behavior of organisms is central for both ecological understanding and species conservation. We used camera traps to monitor the diurnal variation in activity of 3 ubiquitous terrestrial mammals in neotropical forests-nine-banded armadillos (Dasypus novemcinctus), common opossums (Didelphis marsupialis), and red-rumped agoutis (Dasyprocta leporina)-across a fragmented forest landscape of the southern Brazilian Amazon. Results from a total of 3,086 camera-trap days distributed across 21 forest patches (ranging in size from 2 to 14,480 ha) and 2 undisturbed continuous forest areas were used to test the effects of a series of abiotic and forest disturbance variables on species activity. An information theoretic analysis revealed significant predictors of the temporal distribution of activity that varied among species. Habitat fragmentation affected the activity of both nocturnal species, but effects of habitat patch area depended on interactions with disturbance variables for the common opossum. of the 3 species investigated, D. novemcinctus exhibited the greatest variation in activity in relation to forest patch size. Armadillos were strictly nocturnal in forest areas >1,000 ha, whereas their foraging activity switched to a cathemeral pattern, with up to 60% of all photos recorded during the day in smaller forest patches (<1,000 ha). In contrast, the time since forest patches had been isolated was the only significant predictor of activity patterns for agoutis, a diurnal species exhibiting a bimodal activity pattern. Our results support the hypothesis that behavioral plasticity is an important determinant of species persistence in small forest remnants dominated by edge effects. DOI: 10.1644/09-MAMM-A-199.1.
Keywords: Amazon forest; anthropogenic change; behavior; Dasyprocta leporina; Dasypus novemcinctus; Didelphis marsupialis; diel activity; habitat loss; terrestrial mammal